Oral Microbiota of Infants in Maternal Gestational Diabetes: A Systematic Review - Nicole Camoni; Giulio Conti; Alessandra Majorana; Elena Bardellini; Claudia Salerno; Thomas Gerard Wolf; Guglielmo Campus; Maria Grazia Cagetti (MDPI AG, 2024)
Gestational diabetes mellitus (GDM) affects approximately 5-20% of pregnant women and is associated with adverse pregnancy outcomes. This review aimed to assess whether the oral microbiota of infants and their mothers with GDM had a different composition from that found in unaffected women and offspring. PubMed, Embase, Scopus, and Google Scholar were searched in December 2023 after protocol registration in the International Prospective Register of Systematic Reviews (CRD42023406505). Risk of bias was assessed using the Joanna Briggs Institute Critical Appraisal tools. Overall, 1113 articles were identified; after evaluating the full texts, 12 papers were included in the qualitative analysis. In six studies of the eight included, significant differences in microbiota between M-GDM and M-nGDM were found. In four studies, a depletion of Firmicutes and an enrichment of Proteobacteria was found in the microbiota of infants. Since all included studies were judged to have high risk of bias, a quantitative synthesis of the results was not carried out. In conclusion, although the oral microbiota of infants from mothers with GDM could be different from that of infants from mothers without GDM, there is insufficient evidence to clarify this aspect so far.